Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 3 } { 4 } x + 1$
$y = \dfrac { 5 } { 6 } x - 2$
$x$Intercept
$\left ( - \dfrac { 4 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$x$Intercept
$\left ( \dfrac { 12 } { 5 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 2 \right )$
$\dfrac{ 3 }{ 4 } x+1 = \dfrac{ 5 }{ 6 } x-2$
$x = 36$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { 3 } { 4 } } \color{#FF6800}{ x } + 1 = \dfrac { 5 } { 6 } x - 2$
 Calculate the multiplication expression 
$\color{#FF6800}{ \dfrac { 3 x } { 4 } } + 1 = \dfrac { 5 } { 6 } x - 2$
$\dfrac { 3 x } { 4 } + 1 = \color{#FF6800}{ \dfrac { 5 } { 6 } } \color{#FF6800}{ x } - 2$
 Calculate the multiplication expression 
$\dfrac { 3 x } { 4 } + 1 = \color{#FF6800}{ \dfrac { 5 x } { 6 } } - 2$
$\color{#FF6800}{ \dfrac { 3 x } { 4 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ \dfrac { 5 x } { 6 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 12 } = \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 24 }$
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 12 } = \color{#FF6800}{ 10 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 24 }$
 Organize the expression 
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 24 } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$\color{#FF6800}{ 9 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 10 } \color{#FF6800}{ x } = - 24 - 12$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } = - 24 - 12$
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 24 } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
 Find the sum of the negative numbers 
$- x = \color{#FF6800}{ - } \color{#FF6800}{ 36 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 36 }$
 Change the sign of both sides of the equation 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 36 } \right )$
$x = \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 36 \right )$
 Simplify Minus 
$x = 36$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture